1994
DOI: 10.1207/s15327558ijbm0103_2
|View full text |Cite
|
Sign up to set email alerts
|

Lipid lowering through work stress reduction

Abstract: Swedish civil servants, who reported considerable stress while working in larger government authorities, were randomized into either a work stress reduction intervention or a control group. Four work units constituted the intervention group (n = 94). and one unit formed the control group (n = 35). Participants in the two groups were of similar age and two thirds were women. Psychosocial, lifestyle, and physiological assessments were made before, during, and after the 8-month intervention period. A significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 20 publications
2
25
0
1
Order By: Relevance
“…That work stress intervention (i.e., increasing job control) may have a lipid lower effect has been demonstrated. 44 In conclusion, this cross-sectional analysis indicates a possible association between a psychologically demanding job and an unfavorable lipid profile in Japanese male workers. However, at least in the rural setting, the logical basis for the application of the demand-control model to atherogenic lipids is weak.…”
Section: Discussionmentioning
confidence: 62%
“…That work stress intervention (i.e., increasing job control) may have a lipid lower effect has been demonstrated. 44 In conclusion, this cross-sectional analysis indicates a possible association between a psychologically demanding job and an unfavorable lipid profile in Japanese male workers. However, at least in the rural setting, the logical basis for the application of the demand-control model to atherogenic lipids is weak.…”
Section: Discussionmentioning
confidence: 62%
“…In several previous experiments, effects have been documented after group feedback and group intervention on either different aspects of authority over decisions or intellectual discretion (8 p 21 1,32) or social support (26,27). In previously published experiments, decreased (8 p 21 1, 26), as well as increased (32), psychological demands have been reported following the changes.…”
Section: Comments On Fhe Practical Examplementioning
confidence: 95%
“…Most of the published studies have been based upon self-administered questionnaires. One study of cardiovascular risk factors (26) showed that a similar program (which was evaluated in a controlled study) was followed by a reduced ratio of low-density to high-density lipoprotein cholesterol in the experimental group but not in the comparison group. The improvement amounted to 6% -which should be related to the etiologic fraction associated with job strain -accordingly not a bad result!…”
Section: Techniques For Achieving Improved Decision Latitude and Socimentioning
confidence: 99%
“…Since these studies had no reference group, the effects of "regression to the mean" or natural course of stressors or symptoms could not be ruled out (7). A study reported significant improvement in the level of serum lipoproteins after stress reduction activity in an intervention group, in comparison with a reference group (8,9). However, the 2 groups had different base-line levels of serum lipoproteins and work-related factors, and these differences may have been a source of confounding bias.…”
mentioning
confidence: 99%
“…Most previous studies on work stress reduction have assessed acute stress reactions as outcome measures, namely, psychological (eg, anxiety or depression), physiological (eg, blood pressure), and behavioral (eg, smoking, absenteeism, turnover rate) reactions, as well as specific work stressors (1)(2)(3)(4)(5)(6)(8)(9)(10), since a much longer follow-up period is required to observe the onset of illness. Measures of psychological distress and subjective symptoms have been the most frequently used (3, 5, 6, lo), and the studies have generally suggested that these measures are sensitive to a stress reduction program oriented towards the work environment.…”
mentioning
confidence: 99%